2019
DOI: 10.1038/s41535-019-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple low-temperature skyrmionic states in a bulk chiral magnet

Abstract: Magnetic skyrmions are topologically protected nanoscale spin textures with particle-like properties. In bulk cubic helimagnets, they appear under applied magnetic fields and condense spontaneously into a lattice in a narrow region of the phase diagram just below the magnetic ordering temperature, the so-called A-phase. Theory, however, predicts skyrmions to be locally stable in a wide range of magnetic fields and temperatures. Our neutron diffraction measurements reveal the formation of skyrmion states in lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 52 publications
3
68
2
Order By: Relevance
“…As a result, large cooling rates are required to stabilize a significant population of metastable skyrmions in bulk samples (> 40 K/min for 50% skyrmion population in bulk Cu 2 OSeO 3 ) [26]. This presents a limitation to the study and use of metastable skyrmions, which has been previously alleviated using rapid heat pulses from lasers [27] or electrical heaters [28] to form the metastable state, both of which are very energy intensive methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, large cooling rates are required to stabilize a significant population of metastable skyrmions in bulk samples (> 40 K/min for 50% skyrmion population in bulk Cu 2 OSeO 3 ) [26]. This presents a limitation to the study and use of metastable skyrmions, which has been previously alleviated using rapid heat pulses from lasers [27] or electrical heaters [28] to form the metastable state, both of which are very energy intensive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Insulating Cu 2 OSeO 3 (CSO) has gained notable interest due to its magnetoelectric coupling and is considered as an ideal platform to achieve electric field control of SkLs. Recently, an intriguing discovery of a new skyrmion phase (35) and of low-temperature skyrmions (36,37) has been made in CSO crystals, implying richer phase diagrams. The existence of two distinct skyrmion phases in a multiferroic material could be a generic character of underlying physics and may assist in skyrmion manipulation (36).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental findings hint that cubic anisotropy in Cu 2 OSeO 3 also influences the skyrmion nucleation via two different mechanisms [24]: (i) thermodynamically stable skyrmions may appear via rupture formation of metastable spiral states with wave vectors perpendicular to the field (in the case of Cu 2 OSeO 3 along [100] and [010]); (ii) skyrmions may appear in the form of torons [26] (a localized particle consisting of two Bloch points at finite distance and a convex-shaped skyrmion stretching between them) generated by the inhomogeneous magnetic environment provided by the smooth transition from one tilted spiral domain to another [22].…”
Section: Introductionmentioning
confidence: 90%
“…Recently, a new impetus to those theoretical considerations was provided by the reported LT-SkL in the bulk-insulating cubic helimagnet Cu 2 OSeO 3 [22,23]. A LT-SkL was shown to be stabilized by cubic anisotropy for a magnetic field applied along [001] [23,24], the easy direction of the cubic anisotropy [8,21]. Additionally, it was shown that the role of cubic anisotropy is not limited to the SkL stability but also leads to many other remarkable phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation